Game addiction levels of university students in covid-19 pandemic and the effect of pandemic on digital gaming status - Aktaş, Berna; Bostancı Daştan, Nihal (Journal of Dependence, 2021)
Objective: This study aims to reveal the game addiction levels and the effect of the pandemic on digital gaming status in university students during the COVID-19 pandemic.Method: The study sample was calculated as at least 384 individuals using the formula of sample for unknown population, and the study was completed online with 427 students. In the study, students were given an online Questionnaire and the Digital Game Addiction Scale for university students.Results: Of the students, digital game play time was mostly 0-1 hours before (61.1%) and during (52.5%) the pandemic, and 91.1% (n=389) was playing digital games on the phone during the pandemic. Students were mostly playing puzzles and mind games before (58.3%) and during (56.0%) the pandemic, and believing that their digital game play time (47.3%) has not changed during the pandemic. The pandemic has increased the time spent on digital games and increased the play time on combat-strategy games. The average Digital Game Addiction Scale score of the university students was 35.86±16.97. Moreover, 6.3% of the students was in the addicted group, and 1.6% was in the highly addicted group.Conclusion: Comparison of the digital game play times of the students before and during the pandemic showed that this time increased significantly and most of them were on the mobile platform, and that the ratio of playing war-strategy games increased during the pandemic.
Keywords: Covid-19; university; student; game addiction